Prenatal Vaccination Patterns among Birthing Individuals with History of Preterm Birth in the Pre- and Post-COVID Era - Ramey-Collier, Khaila L.; Okunbor, Jennifer I.; Lunn, Siera R.; Feng, Kelvin; Truong, Tracy; Weaver, Kristin E.; Swamy, Geeta K.; Wheeler, Sarahn M. (American Journal of Perinatology, 2023)
Objective This study aims to explore vaccination acceptance among individuals with a history of preterm birth between March and June during the pre-COVID (2019), early-COVID (2020), and late-COVID (2021) periods.Study Design This is a cross-sectional, retrospective cohort study of pregnant individuals with a history of preterm birth (<37 weeks' gestation) who initiated care of a subsequent pregnancy during pre-COVID (March–June 2019), early-COVID (March–June 2020), or late-COVID (March–June 2021). The primary outcome of interest was vaccination status for influenza, Tdap, and COVID-19 vaccines. Fisher's exact and chi-square tests were used to investigate association between vaccination status and time periods, race/ethnicity, and insurance.Results Among 293 pregnancies, influenza vaccination rate was highest in early-COVID (p < 0.05). There was no statistically significant difference in Tdap or COVID-19 vaccination between time periods. COVID-19 vaccination was highest in individuals with private insurance (p < 0.05). There was no statistically significant difference in vaccination status by race/ethnicity.Conclusion In this study on high-risk pregnant individuals, the majority of our cohort remained unvaccinated against COVID-19 into the late-COVID period. Additionally, their influenza vaccination rates were greater than the national average in early-COVID and substantially lower than the national average in late-COVID. This shift in influenza vaccination acceptance may have been sparked by COVID-19 vaccine distribution beginning in January 2021 leading to overall vaccination hesitancy. Standardized guidelines and counseling concerning prenatal safety in recommended immunizations may serve as important tools of reassurance and health promotion.Key Points
Keywords: prenatal vaccination; vaccine hesitancy; COVID-19; preterm birth